PENGECUALIAN PEMBERLAKUAN HUKUM ANTI MONOPOLI BAGI KOPERASI DAN USAHA KECIL DALAM PEMBANGUNAN EKONOMI DI INDONESIA : (Kajian Perspektif al-Siyasah al-Shar’iyah) - Nur Husen, Mohamad; Azizah, Ninik; Syahni, Ahmad (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2022)
This study examines the exception of regulating Anti-monopoly for cooperatives and small businesses. The result of the study shows, firstly: the exception of regulating Anti-monopoly for cooperatives and small businesses is not appropriate, even been out of the frame the philosophical basis of Article 33 of the Act of 1945 because of non-fulfillment aspect of social justice. Secondly, the rationale for antitrust law enforcement exemption for cooperatives and small businesses are more based on the consideration of criteria, roles, and economic impacts of both, which is seen not result in a monopoly and unfair business competition, even though without holding any exception in fact it is common. Thirdly, anti-monopoly law enforcement exemption to cooperatives and small businesses are not suitable with the principle of al-Siyasah al-Shar’iyah, namely maslahah al-‘ammah, as a fundamental principle of maqasid al-shari’ah, therefore, the exception of anti-monopoly law enforcement to cooperatives and small businesses are not only related to cooperatives and small businesses only, but also related to the national interest that includes aspects of national independence, creating an enduring human resources having prediction and also high credibility.